Enhancing Scientific Writing with AI: Evaluating Tools, Practices and Future Implications - Sidra Batool; Muhammad Nadeem Akhtar; Shahbaz Ali Anjum; Rehana Kousar; Amaim Zahid; Mukarram Nawaz (Dialogue Social Science Review (DSSR), 2024)
The integration of Artificial Intelligence (AI) tools in scientific writing has fundamentally transformed how researchers articulate and disseminate their findings. This descriptive review explores a variety of AI applications that enhance the scientific writing process, emphasizing tools that improve clarity, accuracy and efficiency. Key applications discussed include grammar and style checkers, plagiarism detection software, reference management systems, content generation models and data analysis tools. Each of these technologies contributes uniquely to the writing workflow, enabling researchers to produce high-quality manuscripts more efficiently. This review also highlights the numerous benefits of AI integration, such as increased productivity, enhanced writing quality and improved accessibility for non-native English speakers. However, it addresses significant challenges, including the risk of overreliance on AI tools, potential inaccuracies in AI-generated content and ethical concerns surrounding authorship and originality. By analyzing these dimensions, this review underscores the importance of balancing AI assistance with the need for critical evaluation and personal skill development in scientific writing. As AI technologies continue to evolve their impact on the future of scientific communication is likely to grow. This review aims to provide researchers, educators, academicians and institutions with insights into the practical applications and implications of AI tools in scientific writing fostering a deeper understanding of how these innovations can enhance research dissemination while preserving the integrity of scientific work.